Agricultural diversification and smallholders in south asia / edited by P.K. Joshi, Ashok Gulati [and] Ralph Cummings - Joshi, P K (ed.) (New Delhi, 2007)
Pro-poor opportunities are rapidly unfolding in South Asia, spurred by new lifestyles tastes, stimulated by increasing incomes, spreading urbanisation, and expanding globalisation. Dietary patterns are changing of both the poor and the rich, as well as rural and urban consumers, from staple foodgrains to high value-commodities such as fruits, vegetables, milk, meat, eggs, and fish. The real challenge is how to grab these opportunities to alleviate poverty and improve quality of life, particularly for smallholders. This book, comprising contributions by experts from various countries, provides a range of information, analysis, and the beginnings of pathways to accelerate agricultural diversification and facilitate inclusiveness of smallholders through correcting incentives, evolving institutions, and developing infrastructure.
Keywords: Agricultural diversification-south asia